Perbandingan Metode EOQ dan Silver-Meal pada Perencanaan Persediaan Bahan Baku untuk Meminimalkan Biaya Persediaan di PT. Gandum Malang - Oktiarso, Teguh; Mandasari, Revina (Yayasan Lentera Avanya Nagari, 2024)
One of the efforts in improving efficiency is to do inventory control raw materials. If inventory control is running with optimal raw materials companies can minimize the total cost of the inventory. The purpose of this research is to know method planning of raw materials by using the EOQ and Silver-Meal to maintain optimal inventory as well as to determine the scheduling reserved time on the raw material for the next period. The results of the research is that lot size calculation using the EOQ method for tobacco and clove is 2 time reservations, for ambri and etiquette reservations for 5 times bobyn 3 times reservations, for the outer 7 times reservations, for filter 4 times and reservations for the carton box as much as 10 times. As for the lot size calculation by using the method of silver-meal obtained results for all raw materials as much as 12 times the reservation, except tobacco and clove of raw materials as much as 6 times. Finally, the planning of inventory that produces more inventory costs to a minimum on the calculation using silver-meal method is undertaken.